The Peloponnesian War as Total War (De Rebus Antiquis, 2021)
This article delves into the relevance of the concept of “total war” as it is applied to the Peloponnesian War. In so doing, it is noticed a lack of consensus among contemporary scholar in regards to what is required for a war to be considered as total. Therefore, I here advance three sufficient and necessary conditions to deem a warlike conflict as total war. My conclusion, on the one hand, is that the Peloponnesian War fulfilled only part of those conditions. On the other, I hold that the tendency among Hellenists is to constantly compare the two World Wars that ravaged the 20th-century. This distorts the analysis and hampers the explanatory capacity of the concept.
Keywords: Athens; Peloponnesian War; Total War